2016
DOI: 10.5897/jmpr2015.5979
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical screening, total phenolic content and antioxidant activity of some plants from Brazilian flora

Abstract: The present study evaluated the total phenolic and flavonoid content as well as the antioxidant activity of methanolic leaf extracts of five plants from Brazilian flora: Abarema cochliacarpos, Croton corchoropsis, Myroxylon peruiferum, Stryphnodendron pulcherrimum and Tanaecium cyrtanthum by 2,2'-azino-bis-(3-ethylbenzothiazoline-6-sulfonate) (ABTS), 2,2-diphenyl-1-picrylhydrazyl (DPPH) and total antioxidant capacity assays. A thin layer chromatography analysis of all plant extracts has also been performed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
5
0
1
Order By: Relevance
“…The total flavonoid is expressed in mg/g quercetin equivalents (QE). The flavonoid in Ageratum conyzoides leaves in the two extracts are higher than the flavonoids reported for some plants from Brazilian flora (Neto et al, 2016). It is very low when compared to the flavonoids of (Table I) showed that the aqueous extract has significantly (P ˂ 0.05) higher non-flavonoids content than the methanol extract.…”
Section: Discussionmentioning
confidence: 67%
“…The total flavonoid is expressed in mg/g quercetin equivalents (QE). The flavonoid in Ageratum conyzoides leaves in the two extracts are higher than the flavonoids reported for some plants from Brazilian flora (Neto et al, 2016). It is very low when compared to the flavonoids of (Table I) showed that the aqueous extract has significantly (P ˂ 0.05) higher non-flavonoids content than the methanol extract.…”
Section: Discussionmentioning
confidence: 67%
“…The results indicate the strong correlation between the antioxidant activity and the total phenolic compounds content of the analyzed samples (R 2 = 0.995; ρ = 0.997). Several studies point to a strong relationship between the presence of phenolic compounds and antioxidant activity in medicinal plants and fruits [44,45]. A strong correlation between the phenolic compounds content and the photoprotective activity (SPF) was also presented in the analyzed samples (R 2 = 0.954; ρ = 0.977), important data for the future development of photoprotectors from plant extracts that present phenolic compounds as chemical markers, as is the case of the species in study.…”
Section: In Vitro Spf Determinationmentioning
confidence: 78%
“…The ABTS + solution was standardized with the dilution with ethanol to an absorbance of 0.7 (± 0.02) at 732 nm. The absorbance of the samples was measured using 30 µL of the sample solutions (1 mg/mL), added to 3 mL of the standardized ABTS + solution 7 mmol/L, at different time points (6,15,30,45,60 and 120 min) at 734 nm. The inhibition of the oxidation was calculated and plotted as a function of reference antioxidant concentration (Trolox) and expressed as Trolox Equivalent Antioxidant Capacity (TEAC, µmol/L).…”
Section: Inhibition Of 22-azino-bis-(3 Ethylbenzothiazoline)-6-sulfomentioning
confidence: 99%
“…These tests facilitate their quantitative estimation and qualitative separation. Phytochemical screening experiments are commonly performed to promote a guidance of substantial phytochemicals that may be involved in the biological functions of plants [24]. On the other hand, this variation can be linked to the distribution of secondary metabolites, which changes during plant development, environmental stress (drought, poor soil nutrients) as well as strong sunlight [25].…”
Section: Chemical Screeningmentioning
confidence: 99%